Presja środowiska jako determinanta konsumpcji mediów - Bulak, Piotr (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2007)
The Author analyzes the issues related to the consumption of the media, that is to satisfying a range of human needs by means of media reception. The consequence of this analysis may be expressed in the following way: marketing makes people actually work harder than they should in order to earn more money than they need so that they can buy the products they do not really need for money they do not actually have in order to make an impression on their neighbors they do not even like and who are mainly preoccupied with how to impress them most.
Pressure of the environment as the determining factor of media consumption